Analisis Faktor-Faktor Yang Memengaruhi Minat Masyarakat Untuk Melakukan Transaksi Gadai Pada PT. BPR Syari’ah Dinar Ashri Kantor Cabang Aikmel Kabupaten Lombok Timur - Dwi Amelia Haliza; Makhshushi Zakiyah (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2024)
PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency, customers/potential customers from Aikmel sub-district are religious in nature and on average the most preferred and sought after are banks that are based on sharia and also what is most sought after by the community is a fast and reliable process. It's easy, especially since the bank's location is quite strategic, so it's easy for the public to reach/find. The focus of this research is what factors influence people's interest in carrying out pawn transactions at PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency and How the number of people has increased to carry out pawn transactions at PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency. The aim of this research is to describe the factors that influence people's interest in carrying out pawn transactions at PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency and to describe the increase in the number of people carrying out pawn transactions at PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency. This type of research is field research using qualitative methods with a descriptive approach. Data obtained through the process of observation, semi-structured interviews and documentation. Then the data obtained is processed through three stages, namely, data reduction, data presentation, and drawing conclusions. Data validity was carried out by testing data credibility and theory triangulation. The results of this research show that the factors that influence people's interest in carrying out pawn transactions at PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency, its customers must follow the SOPs that apply to PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency. On average, the factors for the people of Aikmel sub-district to carry out sharia pawn transactions are the economic needs of the community and the need for fast funds for children's school fees, daily living costs and business capital. And how to increase customers carried out by PT. BPR Syariah Dinar Ashri Aikmel Branch Office, East Lombok Regency in increasing the gold pawn business is by: Firstly by using product marketing, Second by price marketing, Third by place, and Fourth by means of promotion